Te hahi o te kohititanga marama = The religion of the reflection of the moon : a study of the religion of Te Matenga Tamati : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Religious Studies at Massey University - Elsmore, Bronwyn (Massey University, 1983)
The Kohiti religion was a vital movement in the Wairoa area for more than thirty years. Its positive view and teaching of inclusiveness and unity brought to the believers a hope, a dream, and a promise. It arose in the last years of the nineteenth century - a time when the Maori was at his lowest ebb numerically and culturally. This, then, was also a time of great spiritual need. Te Matenga Tamati received a revelation to guide his people. As the Christian church did not provide a theological system fully acceptable to the Maori, he formulated a faith that did - being a synthesis of traditional beliefs, Old Testament teachings, and Christian values. Taking the new moon as a symbol, the Kohiti made preparations for a great new age to come. Their efforts to construct a great tabernacle to the Lord is an amazing story, and one which clearly demonstrates the belief of the Maori of this period that they were descendants of the house of Jacob. This study begins with an introductory chapter which briefly outlines the Maori response to the gospel up to the period concerned, then examines the reaction in the Wairoa area specifically. Upon this background the whole story of the Kohiti religion is told, and biblical parallels are pointed out. The phenomenology of the movement is then fully considered.
Keywords: Maori (New Zealand people); Millennialism; Tamati, Te Matenga; Māori Masters Thesis; Wairoa (N.Z.); Religion